The HOME (home monitoring of high-risk pregnancies) study: a study protocol for an observational study of a telemedicine-assisted follow-up at home vs. hospitalization - Waldum, Åsa Henning; Pay, Aase Serine Devold; Aasbø, Gunvor; Mishra, Vinod Kumar; Sugulle, Meryam; Staff, Anne Cathrine (Frontiers in Global Women's Health, 2025)
BackgroundPregnancies at high risk for adverse health outcomes for mother and offspring often require long-term antenatal hospitalization and/or frequent outpatient visits. We have developed a telemonitoring home care service for high-risk pregnancies that has been integrated into the Electronic Patient Journal System of our department. We will compare clinical safety, patient-reported outcome measures, and use of healthcare resources compared to standard practice for hospital admissions and/or outpatient visits.MethodThe home monitoring of high-risk pregnancies study is an ongoing observational study. Eligible women with a pregnancy requiring intensified obstetric follow-up (e.g., preterm premature rupture of membranes, hypertensive disorders of pregnancy, or a previous adverse obstetric outcome) are offered study inclusion to either standard care at the hospital or the home telemonitoring group, depending on available home monitoring equipment. Pregnant women included for home monitoring will be telemonitored according to relevant clinical practice for inpatients, including the use of cardiotocography, blood pressure monitoring, C-reactive protein, and temperature measurement, and they will provide self-registration of relevant clinical symptoms. A telecare patient communication system will prompt rapid contact with the hospital in the case of unfavorable registered clinical parameters or subjective symptoms. The home telemonitored women will attend hospital visits for fetal ultrasound assessment at individually assigned intervals. Patients undergoing in-hospital care will serve as the control group in this study and receive standard care. The primary outcome is a composite of severe maternal and perinatal adverse outcomes (sepsis, eclampsia, cerebral hemorrhage, acute respiratory distress syndrome, liver rupture, pulmonary embolism, amniotic fluid embolism, hemolysis, elevated liver enzymes, low platelets, HELLP without hemolysis, and disseminated intravascular coagulation), including fetal or neonatal mortality, maternal mortality, and signs of severe organ damage. Secondary outcomes include other adverse maternal and fetal/neonatal health outcomes, patient-reported outcomes, and economic cost analyses.DiscussionThe implementation of a home care service for women with high-risk pregnancies requiring intensified surveillance is expected to be equally safe and more comfortable and convenient for the women, with lower economic costs.Clinical Trial RegistrationClinicaltrial.gov, NCT05763069.